Successes and failures in producing attentional object-based cueing effects - Irene Reppa (Attention, Perception, & Psychophysics, 2012)
Over 30 years of research using Posner’s spatial cueing paradigm has shown that selective attention operates on representations of spatial locations, leading to space-based theories of attention. Manipulations of stimuli and methods have shown this paradigm to be sensitive to several types of object-based representations—providing evidence for theories incorporating object-based attentional selection. This paper critically evaluates the evidence demanding object-based explanations that go beyond positing spatial representations alone, with an emphasis on identifying and interpreting successes and failures in obtaining object-based cueing effects. This overview of current evidence is used to generate hypotheses regarding critical factors in the emergence and influence of object representations—their generation, strength, and maintenance—in the modulation of object-based facilitatory and inhibitory cueing effects.